2000
DOI: 10.1152/jn.2000.84.4.1708
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency in the Control of Continuous Force Production

Abstract: The purpose of the current investigation was to examine the influence of intermittency in visual information processes on intermittency in the control continuous force production. Adult human participants were required to maintain force at, and minimize variability around, a force target over an extended duration (15 s), while the intermittency of on-line visual feedback presentation was varied across conditions. This was accomplished by varying the frequency of successive force-feedback deliveries presented o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
224
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(255 citation statements)
references
References 25 publications
27
224
2
2
Order By: Relevance
“…Overall, our results reveal a lower complexity (signal noise in its time domain structure) of the force variability without vision, which is consistent with earlier studies showing that the complexity of the force variability decreases when less visual information is provided (Slifkin et al 2000).…”
Section: Effect Of Visual Feedback (Nofb-1 Vs Fb )supporting
confidence: 92%
See 3 more Smart Citations
“…Overall, our results reveal a lower complexity (signal noise in its time domain structure) of the force variability without vision, which is consistent with earlier studies showing that the complexity of the force variability decreases when less visual information is provided (Slifkin et al 2000).…”
Section: Effect Of Visual Feedback (Nofb-1 Vs Fb )supporting
confidence: 92%
“…The success in maintaining the required force target, indeed, has been found to be strongly influenced by the modality (Slifkin et al 2000;Miall et al 1993), delay (Sosnoff and Newell 2007;Miall et al 1985) and gain (number of pixels on the screen per unit of force) with which the visual feedback is shown to the subject (Sosnoff and Newell 2005 , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 2006; Vaillancourt et al 2006). Slifkin et al (2000) investigated the influence of different gains of visual feedback during sustained isometric contraction of the index flexor. The gain was found to be directly correlated to force accuracy (i.e., a precision of force signal with respect to the target) and inversely correlated to force stability (i.e., a degree of force signal fluctuation as the ratio of mean force output over the within-participant standard deviation).…”
Section: Donementioning
confidence: 99%
See 2 more Smart Citations
“…these findings agree with those of previous studies 26,30 , which also reported less precision at higher strength levels. RmS error, used as a precision measure, reflected the subject's difficulty in reaching the target which, in this case, meant reaching the relative torque level required and keeping it constant and continuos.…”
Section: Discussionsupporting
confidence: 93%